Early Detection and Prevention of Sub - Clinical Mastitis in Cows Using TANUVAS - Masti-Guard Kit - N. Bharathy,; P.Vasanthakumar, (The Indian Veterinary Journal, 2025)
A study was conducted in lactating dairy cows in Karur District of Tamil Nadu using MASTI - GUARD kit released by TANUVAS, which comprises of somatic cell count kit and teat protect spray. In the present study, a total of 81 dairy cows owned by 35 progressive dairy farmers who maintained at least 4 dairy cows were selected randomly from five different blocks of Karur district for screening subclinical mastitis. Out of 81 lactating dairy cows screened for sub - clinical mastitis, 44 (54.32%) were positive and 37 (45.68%) were negative. Teat protective spray was applied to 44 animals, which were positive for sub - clinical mastitis. Reduction in somatic cell count were observed in 12 cows (27.27 %) during the first week, 11 (25%) cows during the second week, 16 (36.36 %) cows during the third week, 3 (6.82%) cows during the fourth week whereas in 2 (4.55%) cows during the fifth week, there was no response at all even after a period of five weeks. From this study, TANUCHEK SCC test was found as user friendly and hence it could be used as regular mastitis screening test and to reduce the incidence of sub clinical mastitis in dairy cows by spraying the teat protective liquid spray.